2004
DOI: 10.1074/mcp.m300099-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Tandem Affinity Purification MudPIT to Pathway Proteomics in Yeast

Abstract: A combined multidimensional chromatography-mass spectrometry approach known as "MudPIT" enables rapid identification of proteins that interact with a tagged bait while bypassing some of the problems associated with analysis of polypeptides excised from SDS-polyacrylamide gels. However, the reproducibility, success rate, and applicability of MudPIT to the rapid characterization of dozens of proteins have not been reported. We show here that MudPIT reproducibly identified bona fide partners for budding yeast Gcn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(124 citation statements)
references
References 51 publications
4
119
0
1
Order By: Relevance
“…Methods using LC-MS/MS allow direct identification of peptides (31,35). The MS/MS analysis of Ste2p-Bio-DOPA 1 -␣-factor cross-linked product confirmed that the region Ser 251 -Met , eight b ions representing the N terminus and eight y ions representing the C terminus were identified.…”
Section: Discussionmentioning
confidence: 90%
“…Methods using LC-MS/MS allow direct identification of peptides (31,35). The MS/MS analysis of Ste2p-Bio-DOPA 1 -␣-factor cross-linked product confirmed that the region Ser 251 -Met , eight b ions representing the N terminus and eight y ions representing the C terminus were identified.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, Rtt102p was identified as the newest subunit of both SWI/SNF and RSC complexes by MudPIT or mass spectrometry analysis [17]. The loss of RTT102 created similar phenotypes consistent with the loss of other SWI/SNF subunits [18]. The role of SWI/SNF by all indications is far reaching.…”
Section: Nucleosome Remodeling Complexes Swi/snf Familymentioning
confidence: 99%
“…Two-step purification based on high-affinity interactions of the TAPtag with tag-specific binding resins result in highly purified protein complexes that can be analyzed by mass spectrometry. A number of tandem-affinity tags have been developed [1][2][3][4][5][6]. Here, we describe the procedures for the isolation of protein complexes under native purification conditions using the original TAP-tag developed by the Seraphin group [1,7] ( Fig.…”
Section: Introductionmentioning
confidence: 99%